The shape of the prison sentence on Polish lands from the 15th century until the fall of the Duchy of Warsaw - Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Former Polish law, in terms of broadly understood prison sentences, provided for several significantly different forms of isolation. These differences were a consequence of the entities to which they could be applied, the method of execution, and the consequences of application (disgraceful or non-disgraceful measure). The place where it was performed also varied—it could be dungeons, fortresses, castles, monasteries, prisons, inns rented for this purpose, or the convict’s own home. The penalty of imprisonment, becoming a sanction, clearly accelerated the change from the medieval system of executing penalties, based on corporal punishment, towards modern penal systems, based on isolation, as an independent and dominant penal sanction.
Keywords: history of punishment; prison; criminal law